Doha Development Agenda and Aid for Trade : Supplement. (Policy Papers; Policy Paper ;, 2005)
At their 2005 Spring meetings, the Development Committee and IMFC called on the Bank and Fund to work with others to develop more detailed proposals, for consideration at the Annual Meetings, to help developing countries adjust to and take advantage of the Doha Round. In response, Bank and Fund staff prepared a paper on 'The Doha Development Agenda and Aid for Trade' following a consultation process with donors and least developed countries (LDCs) during the summer. This is a Supplement to the main paper.